Islam, Modernism and the West: Cultural and Political Relations at the End of the Millennium Edited by Gema Martin Munoz, London: J.B. Tauris, 1999, 264 pp. (American Journal of Islam and Society, 1999)
The relations between Muslim peoples and the West, and between Muslimpeoples and forms of modernity, have become increasingly pressing issues ofscholarly and political concern over the past twenty-five years. In part, this isdue to the growing power of Islamism in the lives and politics of many Muslimsocieties and, in part, to the fact that some fonns of Islamism can appear to beprofoundly hostile to all that the West represents. The growing presence ofMuslim peoples in Western societies and the many assumptions which thatpresence calls into question has also caused scholars and politicians to focus onthese relations. Add to this the fact that some leading members of the Westernpolicy establishment, most notably the US political scientist S. P. Huntington, have come to talk in the post-cold war era of a “clash of civilizations” in whichthe clash between Islam and the West is the most profound and the most dangerousfor world p e .This book, which contains sixteen essays by Muslim and non-Muslim scholars,mainly from institutions in Europe and the Arab world, sets out to addresskey issues in the relations between Muslims, modernity, and the West. It is theoutcome of a symposium held in Toledo, Spain, in April 1996, which wasprompted by the Eleni Nakou Foundation for the promotion of cultural contactand understanding among European peoples, and held under the auspices of theJose Ortega y Gasset Foundation. &ma Martin Muiioz, professor of Sociologyof the Arab and Islamic World at the Autonoma University of Madrid was theintellectual “playmaker” of the occasion. Due to its Islamic past and the fundamentalrole it played in transmitting Islamic learning and culture for thedevelopment of Christian Europe, Spain was a goad choice of location for theaonference ...